Auditory-Verbal Therapy as evidence-informed practice (EIP) for infants wearing cochlear implants - Binos, Paris (My University, 2019)
Parents of infants who receive cochlear implants (CIs) have already chosen that their primary concern is how their child will develop spoken language. Infants will develop spoken language comparable to their hearing peers only if they receive the best primary treatment approaches there are today or even better treatment practices which are evidence-informed (EIP). Aim: The aim of this work is to reveal the best clinical practice that SLPs need to implement for handling infants with CIs and whether this clinical approach is EIP.
Keywords: evidence-informed practice; auditory verbal therapy; deaf; speech therapy; rehabilitation; cochlear implant